2009
DOI: 10.1021/ie900014f
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Treatment of Air: Comparison of Various TiO2, Coating Methods, and Supports Using Methanol or n-Octane as Test Pollutant

Abstract: We have investigated the effects of the TiO 2 type and coating method, two important factors for TiO 2 -based photocatalytic purification/deodorization of air. First, two TiO 2 powders (PC500 and 105) designed by Millennium Chemicals for photocatalysis were compared with Degussa P25 TiO 2 , a common reference, for removing methanol or n-octane in a flowing dry mixture of O 2 (20 v/v %) and N 2 . Under the conditions used, the differences were very small. For methanol mineralization, PC500 (the highest surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…In the absence of any synergistic effect between the anatase and rutile mixed TiO 2 phases, it is accepted that anatase is much more active than rutile in the PCO of organic compounds in water and air [43]. Even considering that the smaller crystal size of PC500 (Table 1) may foresee higher density in surface defects [19] reducing the electron-hole recombination time, which ultimately results in lower photocatalytic efficiencies, the larger surface area of PC500 in comparison to P25 which may be related to the higher adsorption capacity may justify the superior activity of PC500 [34,43,44].…”
Section: Catalytic Film Performancementioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of any synergistic effect between the anatase and rutile mixed TiO 2 phases, it is accepted that anatase is much more active than rutile in the PCO of organic compounds in water and air [43]. Even considering that the smaller crystal size of PC500 (Table 1) may foresee higher density in surface defects [19] reducing the electron-hole recombination time, which ultimately results in lower photocatalytic efficiencies, the larger surface area of PC500 in comparison to P25 which may be related to the higher adsorption capacity may justify the superior activity of PC500 [34,43,44].…”
Section: Catalytic Film Performancementioning
confidence: 99%
“…The superior photocatalytic activity of PC500 was attributed to its higher specific surface area (SSA). Taranto et al [19] also reported a slight higher photocatalytic activity of P25 over PC500 in the degradation of methanol and n-octane as gas-phase model pollutants. In another study conducted by Águia et al [13], ten distinct commercially available photocatalysts were incorporated into a water-based exterior paint aiming NO photoabatement.…”
Section: Introductionmentioning
confidence: 95%
“…This relates to the specific surface areas of PC500 and P25 powders (Table 1). Although the crystal size of PC500 is smaller than that of P25 (which may foresee higher density in surface defects [29] and reduce electron-hole recombination time), the larger surface area of PC500 may be related to the higher adsorption capacity, and can justify the superior photocatalytic activity of PC500 [28,30,31].…”
Section: Solar/artificial Uva Pco Of N-decanementioning
confidence: 99%
“…Methanol was chosen as a typical model substance for organic pollutants. [27][28][29] The IMPS measurements have been performed in aqueous electrolytes under variation of the methanol content and the electrode potential, which are expected to be the factors most strongly influencing charge transfer and recombination at the surface. The results reveal quite significant differences between the two surfaces concerning the dominating mechanism of photooxidation, leading to significantly different rate constants for water and methanol photooxidation.…”
Section: Introductionmentioning
confidence: 99%